Asuhan Keperawatan Bersihan Jalan Napas Tidak Efektif Pada Pasien Ny. S Dengan Tb Paru Di Ruang Dahlia RSUD Prof. Dr. Margono Soekarjo Purwokerto - Desta Anggoro Saputri; Tri Sumarni; Tri Martuti (Pena Medika Jurnal Kesehatan, 2023)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis. The method in this case study is descriptive with the subject of one Pulmonary Tuberculosis patient. The pharmacological actions that have been given are Acetulcysteine tab 3x200 mg given IV to relieve phlegm, non-pharmacological measures that are carried out, namely effective coughing and chest physiotherapy which are given every morning for three days. Conclusion: effective cough and chest physiotherapy in clearing blocked airways in Pulmonary Tuberculosis patients. Therefore, it is hoped that nurses can provide effective coughing and chest physiotherapy as non-pharmacological measures to help overcome ineffective airway clearance in patients with pulmonary tuberculosis.